Manhaj Tafsir Al-Kasyaf Karya Al-Zamakhsyari - Asep Mulyaden; Muhammad Zainul Hilmi; Badruzzaman M. Yunus (Jurnal Iman dan Spiritualitas, 2022)
This article aims to find the manhaj of Tafsir al-Kasyaf by Zamakhsyari. Manhaj or the method of interpretation is an essential benchmark in the study of mapping the interpretation methodology. The researchers divide the understanding of the aspects of the technique into four types, namely tahlily, ijmali, maudlu'I, and muqarran. Based on this, the authors want to know more about the Tafsir al-Kasyaf method, both general methods and special methods, with the following discussions: Methods of Interpretation of Tafsir al-Kasyaf and the Systematics of Writing of Tafsir al- Kasysyaf. The authors present a model of Imam az-Zamakhsyari's interpretation of thought in Tafsir al-Kasysyaf because this interpretation significantly influences the wilderness of exegetical thought in the Islamic world. The effect given by this interpretation is not only among the mu'tazilah, but also among the Sunnis who have often rejected the mu'tazilah theology adopted by Imam az-Zamakhsyari.